2022
DOI: 10.3390/ijms232113100
|View full text |Cite
|
Sign up to set email alerts
|

RTCB Complex Regulates Stress-Induced tRNA Cleavage

Abstract: Under stress conditions, transfer RNAs (tRNAs) are cleaved by stress-responsive RNases such as angiogenin, generating tRNA-derived RNAs called tiRNAs. As tiRNAs contribute to cytoprotection through inhibition of translation and prevention of apoptosis, the regulation of tiRNA production is critical for cellular stress response. Here, we show that RTCB ligase complex (RTCB-LC), an RNA ligase complex involved in endoplasmic reticulum (ER) stress response and precursor tRNA splicing, negatively regulates stress-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…These may include tRNAs and initiation and elongation factors. Although we did not obtain evidence of oxidative damage to the latter, we corroborated recently published evidence of ROS-induced tRNA cleavage and fragmentation ( 43 ). In addition to representing a depletion of key translation components, these fragments, likely generated by the RNase angiogenin, are generally considered to be inhibitory to ribosomal function ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These may include tRNAs and initiation and elongation factors. Although we did not obtain evidence of oxidative damage to the latter, we corroborated recently published evidence of ROS-induced tRNA cleavage and fragmentation ( 43 ). In addition to representing a depletion of key translation components, these fragments, likely generated by the RNase angiogenin, are generally considered to be inhibitory to ribosomal function ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…Angiogenin is a tRNA-cleaving RNase that is activated upon a multitude of cellular stress insults to produce translation-inhibiting tRNA fragments ( 41 , 42 ). Activation of angiogenin by menadione and ensuing tRNA cleavage was recently demonstrated ( 43 ). Although these effects may not be the only relevant ones, we conclude that ROS-inducing agents interfere with translation in vivo and in vitro and activate ZAKα and the RSR.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it should be considered that most of the enzymatic activities used in this work to repair anticodon-cleaved nicked tRNAs are present in human cells ( 54 , 55 ). Reversibility of stress-induced nicked tRNA formation in cellulo arises as an exciting possibility ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether oxidation of RNH1 is the principal mechanism of RNH1 dissociation. We have recently reported that there seem to be both oxidative stress‐dependent and ‐independent mechanisms of RNH1 dissociation (Akiyama, Takenaka, et al, 2022). Menadione‐induced RNH1 dissociation from ANG was completely abolished by an antioxidant N‐acetyl‐L‐cysteine, while sodium arsenite‐induced RNH1 dissociation was not affected at all, suggesting that sodium arsenite induces the dissociation of RNH1 in an oxidative stress‐independent manner.…”
Section: Factors Modulating Tdr Biogenesismentioning
confidence: 99%
“…We have recently reported that the RTCB ligase complex (RTCB-LC) negatively regulates tiRNA production (Akiyama, Takenaka, et al, 2022). Under normal conditions, RTCB-LC inhibits tiRNA production likely by sealing a cleaved site before the cleaved (so-called "nicked") tRNAs are separated into 5 0 -and 3 0 -tiRNAs.…”
Section: Othersmentioning
confidence: 99%